Positive psychological trait and career adaptability among millennials / Norsyazwani Muhammad Kamal - Muhammad Kamal, Norsyazwani (Faculty of Business and Management, 2018)
Millennial Generation are born along with technologies improvement, consequently, it has create rapid changes in working structure as well as working environment that requires how they could continuously learn and adapt with new situation on their work future. Thus, in time with increasingly diverse, the ability to navigate and adapt with changes and challenging work are most important components. Career adaptability is a critical variable, which convey meaning the ability to adjust oneself thus, fit with change in their career. Positive psychological traits are major predictors that been recognized as vital capacities on how this students are able to cope with turbulent changes in future work. Therefore, the purpose of this research is to investigate Positive Psychological Traits and Career Adaptability among Millennials as well as to identify the most influential factor in psychological traits that influence career adaptability among students at UiTM Bandaraya Melaka. This study used convenience sampling techniques and online questionnaire as an instrument to collect data. The data from 70% out of 329 students are collected then evaluated by using Statistical Package for the Social Science (SPSS) Version 22 Software. The result from Multiple Regression analysis indicates that all the elements in positive psychological traits which is resilience, optimism and hope have positive significant relationship with career adaptability. Moreover, Regression analysis revealed that, resilience found to be the most influential variables towards career adaptability among millennials at UiTM Cawangan Melaka Kampus Bandaraya.